Advances in allogeneic stem cell transplantation in the combined immunotherapy of the hematological malignances and solid tumors - Mackiewicz, Andrzej; Iżycki, Dariusz; Nawrocki, Sergiusz (Contemporary Oncology/Współczesna Onkologia, 2002)
Allogeneic stem cell transplantation was developed as a method to rescue hematopoietic function following high dose myeloablative radio-and chemiotherapy in the treatment of hematological malignances. Most recently investigators recognized that anti-neoplastic GVL and GVT effects can be induced by donor-originated T cells transplanted with allogeneic stem cells and that curative potency of these effects may be enhanced by donor lymphocytes infusion. Current investigations are focused on i) application of combined anticancer immuntherapy in the order to enhance specific antitumor immune response and ii) development of clinical approaches to diminishing Graft Versus Host Disease. The first goal can be accomplished by immunization of the donor of allogenetic stem cells with gene modified tumor vaccines in the order to induction of antitumor specific effector and memory cells. The second one assumes the induction of anergy of the potential alloreactive T-cell by application of CTLA-4 monoclonal antibody responsible for the CD28 costimulatory molecule blockade. The major challenge of these approaches is to obtain selective blockade of Graft Versus Host Disease without compromising Graft Versus Tumor effects. We review here the development and early clinical results of allogeneic stem cell transplantation and donor lymphocyte infusion as potential immunotherapy for hematological maligannces and solid tumors. Moreover, we discuss the future strategies which include ex vivo generation of tumor-specific T-cells of the donor followed their adoptive transfer in the order to enhance antitumor immune response of recipient.